O infinito: um obstáculo no estudo da Matemática - Amadei, Flavio Luiz (2005)
The research here presented approaches the notion of infinite under some different views, with the main purpose of indicating how imbricated was its formation as a mathematical concept and its consequences to the learning of mathematics. This research is supported by bibliographical study, presentation and analysis of the literature currently available on this subject. Some introductory mathematical concepts are presented on the notion of infinite, some aspects of the historical evolution of this notion in Mathematics, with special consideration to Bolzano s work The Paradoxes of Infinite , and data from other researches in the field of Mathematics Education. Analysis that intent to underline relationships between the epistemological and historical process of the notion of infinite, specially actual infinite, and the developmental process of human thinking in the learning of Mathematics, are presented as a conclusion